2017
DOI: 10.2196/jmir.6639
|View full text |Cite
|
Sign up to set email alerts
|

Sugarsquare, a Web-Based Patient Portal for Parents of a Child With Type 1 Diabetes: Multicenter Randomized Controlled Feasibility Trial

Abstract: BackgroundRaising a child with type 1 diabetes (T1D) means combining the demands of the disease management with everyday parenting, which is associated with increased levels of distress. A Web-based patient portal, Sugarsquare, was developed to support parents, by providing online parent-professional communication, online peer support and online disease information.ObjectiveThe first aim of this study was to assess the feasibility of conducting a multicenter, randomized controlled trial in Dutch parents of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 59 publications
0
59
0
Order By: Relevance
“…Participants in 12 articles (Bolyai, Bova, Lee, & Gruppuso, 2011;Bolyai, Bova, Lee, & Johnson, 2012;Bolyai et al, 2010;Bolyai et al, 2004;Grey, Jaser, Whittemore, Jeon, & Lindemann, 2011;Hoff et al, 2005;Kichler, Kaugars, Marik, Nabors, & Alemzadeh, 2013;Mackey, Herbert, Monaghan, & Cogen, 2016;Monaghan, Hilliard, Cogen, & Streisand, 2010;Nansel et al, 2009;Wysocki et al, 2007;Wysocki et al, 2000) were reported to be recruited mainly from children' hospitals, diabetes centers, or endocrinology clinics in the United States, whereas parents in other articles were from Greece (Tsiouli, Pavlopoulos, Alexopoulos, Chrousos, & Darviri, 2014), Germany (Saßmann et al, 2012), the UK (Doherty, Calam, & Sanders, 2013), the Netherlands (Boogerd et al, 2017), and Iran (Saghaei, Omidi, Dehkordi, & Safavi, 2017). There were two studies (Kichler et al, 2013;Nansel et al, 2009) including children and parents as participants, one study (Bolyai et al, 2011) focused on fathers only, two studies (Bolyai et al, 2004;Saghaei et al, 2017) included mothers only, and the rest included both parents as participants.…”
Section: Participants and Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Participants in 12 articles (Bolyai, Bova, Lee, & Gruppuso, 2011;Bolyai, Bova, Lee, & Johnson, 2012;Bolyai et al, 2010;Bolyai et al, 2004;Grey, Jaser, Whittemore, Jeon, & Lindemann, 2011;Hoff et al, 2005;Kichler, Kaugars, Marik, Nabors, & Alemzadeh, 2013;Mackey, Herbert, Monaghan, & Cogen, 2016;Monaghan, Hilliard, Cogen, & Streisand, 2010;Nansel et al, 2009;Wysocki et al, 2007;Wysocki et al, 2000) were reported to be recruited mainly from children' hospitals, diabetes centers, or endocrinology clinics in the United States, whereas parents in other articles were from Greece (Tsiouli, Pavlopoulos, Alexopoulos, Chrousos, & Darviri, 2014), Germany (Saßmann et al, 2012), the UK (Doherty, Calam, & Sanders, 2013), the Netherlands (Boogerd et al, 2017), and Iran (Saghaei, Omidi, Dehkordi, & Safavi, 2017). There were two studies (Kichler et al, 2013;Nansel et al, 2009) including children and parents as participants, one study (Bolyai et al, 2011) focused on fathers only, two studies (Bolyai et al, 2004;Saghaei et al, 2017) included mothers only, and the rest included both parents as participants.…”
Section: Participants and Study Characteristicsmentioning
confidence: 99%
“…The rest were conducted mainly by experienced and "licensed" psychologists or specially trained college students. Participants of three studies (Boogerd et al, 2017;Mackey et al, 2016;Nansel et al, 2009) received telephone-based or web-based parenting interventions.…”
Section: The Content Of Interventionmentioning
confidence: 99%
See 3 more Smart Citations